BIMBINGAN SISWA SD MENJADI TERANG DAN GARAM DI SEKOLAH HIDUP DALAM NILAI-NILAI KRISTIANI - Afari Sarumaha (Counseling For All : Jurnal Bimbingan dan Konseling, 2025)
Counseling guidance in Elementary Schools plays a crucial role in shaping students' character based on Christian values. One of the main goals of counseling is to help students become the "salt and light" in their environment, as taught in Matthew 5:13-16. Through an approach rooted in love and Christian principles, counselors guide students to internalize values such as love, honesty, humility, and integrity. With consistent guidance, students are expected to demonstrate Christian character in their daily lives, both at school and outside of school. This article explores how Christian counseling can strengthen students' character in elementary schools and help develop them into individuals who have a positive impact on the school environment. Additionally, this article discusses the moral and spiritual challenges students face in a constantly changing world, and how Christian counseling serves as an essential platform for shaping a generation that is not only academically intelligent but also possesses integrity and the character of Christ